Ecophysiology of species with distinct leaf morphologies: Effects of plastic and shadecloth tree guards - Close, D.; Ruthrof, K.; Turner, S.; Rokich, D.; Dixon, Kingsley (Blackwell Science Inc., 2009)
Ecological restoration using seedling tubestock is challenging under a Mediterranean-type climate of hot, dry summers. We investigated the ecophysiological effects of plastic tree guards and shadecloth tree guards during seedling establishment of four co-occurring tree species that differ in leaf morphology. Average temperature was 6.7°C higher in plastic guards than controls over a summer, with a maximum of 53.5°C compared to 47.9°C in controls. Light levels were 2-fold lower in both tree guard treatments relative to control. In spring, photosynthesis and specific leaf area were significantly elevated in shadecloth tree guards relative to other treatments. In summer, photosynthetic rate was significantly lower, and midday photochemical efficiency was significantly higher, in both tree guard treatments relative to controls. The effect of elevated temperature in plastic tree guards may partially explain our results of higher mortality of seedling in plastic tree guards. The relatively elevated spring photosynthesis of seedlings in shadecloth tree guards may partially explain the result of reduced mortality and increased growth in this treatment. We conclude that shadecloth tree guards create a microclimate more favorable for seedling establishment in a Mediterranean-type environment than plastic tree guards and control treatments. Our results may have wide applicability to the range of restoration settings where seedling tubestock is planted, except in environments where low temperature is limiting to plant growth. © 2007 Society for Ecological Restoration International.